High-smoothness pullulan empty capsule and method for improving smoothness of pullulan empty capsule

By controlling the conductivity of Plulandosugar and introducing the connector reagent to form a cyclized structure, the glue viscosity and electrostatic problems caused by high molecular weight Plulandosugar are solved, and the high slippage and good mechanical properties of Plulandosugar shell are achieved.

CN119499206AActive Publication Date: 2025-02-25JIANGSU LEFAN CAPSULE
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411742668.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The high molecular weight Plulandosaccharide increases the viscosity of the gel liquid, affects dispersion, resulting in internal friction and electrostatic effects inside the gel liquid, limiting the effects of lubricants and plasticizers, and unable to fundamentally improve the smoothness of the capsule shell.

Method used

By controlling the conductivity of the plulandosaccharide in the range of 0.1 ms/cm to 0.8 ms/cm, and introducing specific linker reagents, such as sodium periodate, cystine and diamino polyethylene glycol, the plulandosaccharide with a cyclized structure is formed, reducing the intermolecular winding and friction.

Benefits of technology

The surface smoothness of the Prulan hollow capsule shell is significantly improved, the friction force is reduced, the surface microstructure of the film is improved, and the smoothness and mechanical properties of the capsule shell are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499206A_ABST
    Figure CN119499206A_ABST
Patent Text Reader

Abstract

The invention discloses a high-smoothness pullulan empty capsule and a method for improving the smoothness of the pullulan empty capsule, the surface smoothness of a prepared pullulan capsule shell is improved by controlling the conductivity of pullulan polysaccharide in a range of 0.1 ms / cm to 0.8 ms / cm for the first time; by adopting small-molecular-weight pullulan with the molecular weight of 1-600,000 Daltons and introducing sodium periodate, cystine and diamino polyethylene glycol as a linker reagent, the pullulan is subjected to end-to-end connection cyclization, so that winding and friction among pullulan molecules are reduced, the friction force of a capsule shell is reduced fundamentally, and the surface smoothness of the capsule shell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine, and particularly relates to a high-slippery pullulan hollow capsule and a method for improving the slippery pullulan hollow capsule. Background Art

[0002] Pullulan hollow capsules, also known as pullulan hollow capsules, are hollow capsules made from pullulan. Pullulan is a natural polysaccharide produced by fermentation of Aureobacidium pullulans. It is a non-animal-derived polymer material with no potential risk of residual hormones or drugs in the body. It has the unique advantages of being non-toxic, odorless, biodegradable, and having excellent oxygen barrier properties. It has been widely used in the fields of medicine and health products, especially in the need to protect sensitive ingredients, improve bioavailability, and meet vegetarian requirements.

[0003] The surface smoothness of hollow capsules is an important parameter in its quality control. It directly affects the filling efficiency and appearance quality of the capsules on the automatic filling machine. Therefore, it has always been the focus of research by manufacturers. The existing production process of pullulan hollow capsules mainly improves its surface smoothness by controlling the raw material formula, production process and quality inspection standards. In terms of raw material formula, pullulan is mainly mixed with carrageenan to improve the surface smoothness of the capsule shell, or plasticizers and lubricants are added to the glue to reduce the viscosity of the pullulan and carrageenan solution, increase its flexibility and surface smoothness; in terms of production process, it is mainly to accurately control the ratio of pullulan, carrageenan, plasticizer, lubricant and water, heating and insulation time, etc., to ensure the uniformity and viscosity of the glue, and control the parameters of drying and pressing to ensure the molding quality of the capsule shell; the quality inspection standard is mainly to detect the thickness and water content of the capsule shell, because studies have shown that the thickness and water content of the capsule shell have a significant effect on the adhesion of the capsule.

[0004] Experiments show that the use of lubricants is crucial to improving the surface smoothness of capsule shells. It can not only reduce the friction of capsule shells on the filling machine, but also reduce the generation of static electricity and improve the physical properties of capsule shells. In actual production, commonly used lubricants include glycerin, magnesium stearate, sorbitol, propylene glycol, polyethylene glycol, vegetable oil, etc. The action mechanism of these lubricants can be roughly divided into two categories. One is to reduce the friction of the capsule shell, reduce the friction on the filling machine, ensure smooth capsule feeding and filling, reduce blockage and wear, reduce the adhesion of drug powder on the surface of the capsule shell, keep the capsule shell clean and smooth, and improve the appearance of the final product; the other is to reduce the cohesion between pullulan and related component molecules, improve material fluidity, reduce intermolecular electrostatic effects, so as to improve the fluidity and uniformity of the rubber during processing, thereby improving the smoothness of the capsule shell surface and making the capsule appearance smoother and more beautiful.

[0005] However, in order to ensure the gas barrier and impact resistance of the capsule, the existing pullulan capsules use pullulan raw materials with high molecular weight. For example, CN108721632A discloses a high molecular weight pullulan additive and its application in capsule preparation. High molecular weight pullulan is mixed with gellan gum to make capsules. The weight average molecular weight of pullulan is ≥1.8×10^5 (i.e. ≥180,000 Daltons), specifically 771200, which is significantly higher than the molecular weight of standard pullulan. Pullulan is formed by two α-1,4-glycosidic bonds connecting α-D-glucose rings to form maltotriose, and the two ends are then combined with other maltotriose by α-1,6-glycosidic bonds. Such repeated connections form a linear macromolecule. Therefore, although high molecular weight pullulan as a raw material can ensure the mechanical properties of the prepared capsule shell, it also increases the viscosity of the glue, especially affects the dispersion of pullulan, making it easy for cross-linking and entanglement between its molecules, resulting in a certain inherent friction and electrostatic effect inside the glue, which limits the role of added lubricants, plasticizers, etc., and cannot fundamentally improve the slipperiness of the capsule shell.

[0006] In addition, conductivity, also known as electrical conductivity, is an important indicator for detecting capsule shell quality control. It is generally used to evaluate the dissolution rate of the capsule shell, the compatibility of the capsule shell with the contents, and the control level of the capsule shell's hygroscopicity, water content, aldehydes and trivalent metal ion impurities. In existing studies, there is no report on the relationship between conductivity and capsule shell surface slipperiness. Summary of the invention

[0007] In view of the fact that the use of the above-mentioned high molecular weight pullulan as a raw material increases the viscosity of the glue, affects dispersion, and makes it easy for cross-linking and entanglement to occur between its molecules, resulting in certain inherent friction and electrostatic effects inside the glue, and the problem that the added lubricant, plasticizer, etc. cannot fundamentally improve the slipperiness of the capsule shell, the present invention provides a method for improving the slipperiness of hollow pullulan capsules, and explores the effect of the electrical conductivity of the raw materials on the surface slipperiness of the capsule shell. The present invention controls the surface slipperiness of the prepared pullulan capsule shell for the first time by controlling the electrical conductivity of pullulan; in addition, by controlling the molecular weight of pullulan within a relatively low range and introducing a specific linker reagent, the straight-chain pullulan is cyclized by connecting the head and tail, thereby reducing the entanglement and friction between pullulan molecules, fundamentally reducing the friction of the capsule shell, and improving the smoothness of its surface. The specific technical scheme is as follows: Firstly, the present invention provides a high-slippery pullulan hollow capsule, wherein the conductivity of the pullulan polysaccharide used in the hollow capsule is controlled within the range of 0.1 ms / cm to 0.8 ms / cm.

[0008] The aforementioned high-slippery pullulan hollow capsule is prepared from the following components by mass fraction: 75-90wt% pullulan polysaccharide, 0.5-5wt% gelling agent, 0.01-0.15wt% moisturizing agent, 0.1-1wt% lubricant, and the balance is pure water.

[0009] Preferably, in the aforementioned high-slippery pullulan hollow capsules, the molecular weight of the pullulan polysaccharide is controlled at 100,000 to 600,000 Daltons, wherein the pullulan polysaccharide below 100,000 Daltons and above 500,000 Daltons accounts for no more than 20%, and the average molecular weight is 250,000 to 350,000 Daltons.

[0010] Further preferably, in the aforementioned high-slippery pullulan hollow capsules, the pullulan is a pullulan with a cyclized structure formed by treating with a cyclization linker composition; the cyclization linker composition is composed of sodium periodate, cystine and diaminopolyethylene glycol, wherein: the amount of sodium periodate is 0.01% to 0.1% of the weight of the pullulan; the amount of cystine is 1% to 5% of the weight of the pullulan; the amount of diaminopolyethylene glycol is 5% to 10% of the weight of the pullulan.

[0011] Further preferably, in the aforementioned high-slippery pullulan hollow capsules, among the components of the cyclized linker composition, the amount of sodium periodate is 0.01% to 0.05% of the weight of pullulan polysaccharide; the amount of cysteine ​​is 1% to 2% of the weight of pullulan polysaccharide; the amount of diaminopolyethylene glycol is 5% to 6% of the weight of pullulan polysaccharide; and the molecular weight of the diaminopolyethylene glycol is preferably 5k to 10k Daltons.

[0012] In the aforementioned high-slippery pullulan hollow capsules, the gelling agent is one or a mixture of curdlan, gellan gum, carrageenan, locust bean gum, pectin, xanthan gum, and konjac gum; the moisturizing agent is one or a mixture of glycerol, sorbitol, glycerol, fructose alcohol, triethyl citrate, and docusate sodium; the lubricant is one or a mixture of sodium stearyl fumarate, sucrose ester, corn starch, colloidal silicon dioxide, magnesium stearate, poloxamer, copovidone, and stearyl palmitin.

[0013] Secondly, the present invention provides a method for improving the slipperiness of pullulan hollow capsules, comprising the following process steps: 1) Pullulan preparation: Prepare or directly weigh pullulan with a molecular weight range of 100,000 to 600,000 Daltons, wherein pullulan below 100,000 Daltons and above 500,000 Daltons accounts for no more than 20%, and the average molecular weight is 250,000 to 350,000 Daltons; use sodium periodate, cystine and diamino polyethylene glycol as a linker composition to treat the pullulan to form a cyclized structure; and detect its conductivity, which is controlled within the range of 0.1 ms / cm to 0.8 ms / cm; 2) Material ratio: Weigh 75-90wt% of pullulan with a cyclized structure, 0.5-5wt% of a gelling agent, 0.01-0.15wt% of a moisturizing agent, 0.1-1wt% of a lubricant, and the remainder of cold pure water, a total of 100 parts; 3) Preparation of glue: Add the gel to cold pure water and stir, raise the temperature to above 90°C and incubate for 30-90 minutes until it is completely dissolved, then add the moisturizer and lubricant and continue to stir until it is completely dissolved, finally add pullulan and incubate until it is completely dissolved to form a gel solution, keep it stable at 50-60°C and set aside; 4) Glue dipping molding: The stabilized glue liquid is dipped into a mold for molding, and quickly dried in an oven at 40-45°C for 20-60 minutes to obtain a capsule cap body rubber blank, which is demoulded, cut and fitted using a demoulder to obtain a high-slippery pullulan hollow capsule.

[0014] As a preferred technical solution, in step 1), the process of using sodium periodate, cystine and diamino polyethylene glycol as a linker composition to treat pullulan to form a cyclized structure is as follows: 1-1) dissolving pullulan in distilled water, adding 0.01% to 0.1% sodium periodate by weight of pullulan, controlling the reaction temperature to 0 to 8°C, the pH value to 5.0 to 5.5, and reacting for 6 to 20 hours under light-shielding conditions. After the reaction is completed, removing unreacted sodium periodate to obtain an oxidized pullulan solution; 1-2) adding cystine in an amount of 1% to 5% by weight of the pullulan to the oxidized pullulan solution, carrying out a condensation reaction for 4 to 8 hours at room temperature while keeping the pH constant, to form a condensed pullulan solution; 1-3) Adding 5% to 10% of the weight of pullulan diaminopolyethylene glycol to the condensed pullulan solution and reacting for 2 to 6 hours to obtain a pullulan molecule with weak head-to-tail cyclization; 1-4) Purify the cyclized pullulan and test the product to ensure that its purity is 99% or above for later use.

[0015] As a preferred technical solution, in step 3), the specific process of preparing the glue solution is as follows: 3-1) Add the gelling agent into cold pure water and stir until dissolved at a stirring speed of 60-120 r / min, then heat the solution to above 90°C and incubate for 1 hour; 3-2) Add moisturizer and lubricant, stir until completely dissolved, stirring speed is 60-120r / min; 3-3) Add the cyclized pullulan, stir evenly and incubate for 4 to 5 hours, stirring once every hour at a stirring speed of 60 to 120 r / min; 3-4) After the pullulan is completely dissolved, keep it at 50-60℃ for 2-3 hours to prepare for dipping and molding.

[0016] As a further preferred technical solution, in step 3-1), the temperature for dissolving and incubating the gel is 90-98°C. Experiments have shown that when the temperature of the gel is raised to this temperature, the gel dissolves better.

[0018] Beneficial effects of the present invention: 1) The present invention proposes for the first time the concept of improving the surface smoothness of the prepared pullulan capsule shell by controlling the conductivity of pullulan polysaccharide. By controlling the conductivity of pullulan polysaccharide within the range of 0.1 ms / cm to 0.8 ms / cm, it is ensured that the pullulan polysaccharide is relatively completely dissolved and the film-forming texture is uniform, thereby improving the surface smoothness of the prepared film.

[0019] 2) The present invention controls the molecular weight of pullulan to 100,000-600,000 Daltons, wherein the proportion of pullulan below 100,000 Daltons and above 500,000 Daltons does not exceed 20% (about 300,000 Daltons on average). The entanglement and friction between small molecular weight pullulan molecules are small, which is conducive to dispersion. The small molecular weight pullulan has a small effect on the auxiliary material components, which is easy to mix evenly, thereby improving the smoothness of the surface of the prepared capsule shell.

[0020] 3) The present invention introduces a specific linker reagent to cyclize the straight-chain pullulan by connecting the end to the end, making it easier for the molecules to slide, thereby avoiding cross-linking and entanglement between pullulan molecules, further reducing the entanglement and friction between pullulan molecules, fundamentally reducing the entanglement friction between capsule shell materials, and further improving the smoothness of its surface.

[0021] 4) The present invention uses sodium periodate + cystine + diamino polyethylene glycol as a pullulan linker composition to achieve the head-to-tail weak connection cyclization of pullulan molecules, wherein sodium periodate is used to oxidize pullulan to form oxidized pullulan containing two carbonyl groups; cystine contains a free thiol group (-SH), which can undergo a condensation reaction with the carbonyl group of oxidized pullulan to form a thiol bond, and diamino polyethylene glycol can further react with cystine to form a stable ring structure, thereby achieving the head-to-tail connection of pullulan molecules. The reaction principle is clear, the technical route is simple, the reaction process is controllable, and it has good practical value.

[0022] 5) The present invention precisely controls the dosage and reaction conditions of sodium periodate, the added amount is 0.01% to 0.1% of the weight of pullulan, and the reaction temperature is controlled to be 0 to 8°C, the pH value is 5.0 to 5.5, and the reaction is carried out for 6 to 20 hours under light-shielding conditions, so that it only oxidizes the carbon-carbon bond between the adjacent hydroxyl groups at the end of the pullulan chain, and the introduction of cystine and diamino polyethylene glycol is targeted at the specific position of the oxidized pullulan. This specific modification will not interfere with other areas of the pullulan, and achieves head-to-tail connection, which ensures the integrity of the pullulan structure and ensures the gas barrier advantage of the capsule. Secondly, the cyclized pullulan has better three-dimensional elasticity than the directly connected pullulan, which can improve the internal impact resistance of the capsule shell.

[0023] 6) In the linker reagent composition introduced by the present invention, sodium periodate only oxidizes the ends of pullulan, and unreacted sodium periodate will be removed, which will not affect its structure and safety. Cystine itself is widely present in the body, and its introduction in the cyclization reaction of pullulan only targets the two ends of the oxidized pullulan, and will not have a negative impact on the safety of the capsule. Diaminopolyethylene glycol is a commonly used biocompatible polymer with good water solubility and biocompatibility, and is often used in drug delivery systems. Therefore, it will not affect the safety of pullulan, thereby ensuring the application of the prepared hollow capsules in the field of medicine and health care products. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the molecular structure of pullulan; Figure 2 This is a surface microscope photo of the pullulan hollow capsule 2 prepared in Example 3 of the present invention; Figure 3This is a surface microscope photo of the pullulan hollow capsule 3 prepared in Example 4 of the present invention; Figure 4 This is a surface microscope photo of the pullulan hollow capsule 4 prepared in Example 5 of the present invention; Figure 5 This is a surface microscope photograph of the comparative hollow capsule 10 prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments.

[0026] Example 1 This embodiment is a method for preparing cyclized pullulan. Figure 1 As shown in the figure, pullulan is formed by connecting α-D-glucose ring with two α-1,4-glycosidic bonds to form maltotriose, and the two ends are then connected to other maltotriose with α-1,6-glycosidic bonds, and the two ends are repeatedly connected to form a linear macromolecule with a molecular weight of up to several million Daltons. In the prior art, in order to ensure the impact resistance of the capsule shell, high molecular pullulan is often used. However, high molecular pullulan molecules are prone to cross-linking and entanglement, and there is a certain inherent friction and electrostatic effect inside the glue. The glue has high viscosity and poor dispersibility, which affects the surface microstructure of the film. The added lubricant and plasticizer cannot fundamentally solve this problem, so it is difficult to further improve the surface slipperiness of the capsule shell. In order to solve this problem, this embodiment provides a measure to prepare a cyclic pullulan with weak head-to-tail connection through a linker composition, thereby reducing the entanglement and friction between pullulan molecules, fundamentally reducing the friction of the capsule shell, improving its surface microstructure, and thus improving the smoothness of the capsule shell surface.

[0027] In this embodiment, sodium periodate + cystine + diaminopolyethylene glycol are used as the pullulan linker composition. Among them, sodium periodate can be used to oxidize pullulan. Sodium periodate is a strong oxidant, which specifically oxidizes the carbon-carbon bond between adjacent hydroxyl groups. By precisely controlling the concentration of sodium periodate and the reaction conditions, only the carbon-carbon bond between adjacent hydroxyl groups at the end of the pullulan chain can be oxidized to form an oxidized pullulan containing two carbonyl groups; cystine contains a free thiol group (-SH), which can undergo a condensation reaction with the carbonyl group of the oxidized pullulan to form a thiol bond, and diaminopolyethylene glycol can further react with cystine to form a stable ring structure. The reaction process is as follows: Both ends of the pullulan polysaccharide chain + sodium periodate → oxidized pullulan (containing carbonyl groups at both ends), Oxidized pullulan + cystine (-SH) → intermediate product of the carbonyl groups at both ends of oxidized pullulan connected by thioketone bonds. Intermediate product + diaminopolyethylene glycol (PEG(NH2)2) → head-to-tail linked cyclized pullulan.

[0028] In this embodiment, in order to ensure the joint strength and the impact resistance of the pullulan capsule, the molecular weight of the diaminopolyethylene glycol is preferably 5k-10k Daltons. To ensure that sodium periodate only oxidizes the two ends of pullulan, the amount of sodium periodate added is controlled to be 0.01%-0.1% of the weight of pullulan, preferably 0.01%-0.05%, and the reaction temperature is controlled to be 0-8°C, the pH value is 5.0-5.5, and the reaction is carried out under shading conditions for 6-20 hours. After the reaction is completed, the unreacted sodium periodate and glycerol are removed by ultrafiltration to ensure the safety of the product.

[0029] The cyclized pullulan molecules in this embodiment are easier to slide, thereby avoiding cross-linking and entanglement between pullulan molecules, further reducing the entanglement and friction between pullulan molecules, fundamentally reducing the entanglement friction between capsule shell materials, and further improving the smoothness of its surface. It not only realizes the weak connection cyclization of pullulan molecules at the head and tail, but also improves the slipperiness of pullulan capsules. At the same time, the joint composition used in this embodiment does not affect the performance of pullulan. Sodium periodate is a strong oxidant. Under reasonable control of dosage and reaction conditions, the oxidation of pullulan is controllable and will not affect the safety of pullulan. It ensures that the capsule shell has the proper gas barrier properties, and the cyclized pullulan has better three-dimensional elasticity than the directly connected pullulan, which can improve the internal impact of the capsule shell. Cystine is a sulfur-containing amino acid, and its thiol (-SH) is reducing, which can form a thiol bond with the oxidized pullulan, and cystine itself is widely present in the body and is generally considered to be safe, so it will not have a negative impact on the safety of the capsule. Diaminopolyethylene glycol is a commonly used biocompatible polymer. Due to its good water solubility and biocompatibility, it is often used in drug delivery systems. Therefore, the use of diaminopolyethylene glycol in the cyclization of pullulan capsules is also safe.

[0030] In this embodiment, the amount of sodium periodate is 0.01% of the weight of pullulan, the amount of cystine is 1% of the weight of pullulan, and the amount of diaminopolyethylene glycol is 5% of the weight of pullulan. The specific process of cyclic pullulan is described in detail below: First, prepare small molecule pullulan. It was found through experiments that the entanglement and friction between small molecular weight pullulan molecules are small, which is conducive to dispersion, and the effect between small molecular weight pullulan and auxiliary material components is small, which is convenient for uniform mixing, and thus the smoothness of the prepared capsule shell surface can be improved to a certain extent. In this embodiment, the pullulan purchased from the market (Hebei Runying Biotechnology Co., Ltd., Yujian Kangyuan, 091), with a molecular weight of 20,000 Daltons to 2 million Daltons, was treated with pullulanase to obtain small molecular weight pullulan. The specific process of enzymolysis can refer to the prior art, or the following preparation method can be adopted: 1000g of pullulan is configured to a concentration of 6% (w / v), the pH is adjusted to 5.2, and heated at 58°C for 30 minutes for pre-gelatinization; 2g of pullulanase (200 ASPU / g) is added for treatment. During the treatment, the molecular weight distribution of pullulan after enzyme treatment is recorded, with a molecular weight between 100,000 and 600,000 Daltons, and a molecular weight of less than 100,000 Daltons and more than 500,000 Daltons. The proportion of pullulan polysaccharides does not exceed 20%, and the average molecular weight is preferably 300,000 Daltons, so as to ensure that the prepared pullulan hollow capsules have suitable hardness and impact resistance. After the enzymolysis is completed, centrifuge at 3000 r / min for 3 minutes and collect the centrifugal precipitate, wash it 3 times with ethanol aqueous solution, and finally freeze-dry it. In other embodiments, pullulan polysaccharides with a molecular weight of 25 to 35 Daltons (for example, a molecular weight of 300,000 Daltons) can also be directly used as a raw material.

[0031] Then, 1000 g of pullulan with a suitable molecular weight is dissolved in distilled water, the reaction temperature is controlled to be 4°C and the pH value is 5.5, 0.1 g of sodium periodate is added, and the reaction is carried out for 16 hours under light-shielding conditions to oxidize the carbon-carbon bond between adjacent hydroxyl groups at the end of the pullulan chain to form an oxidized pullulan containing two carbonyl groups; after the reaction, the unreacted sodium periodate is removed by ultrafiltration (filter membrane 0.22 μm to 0.45 μm); 10 g of cysteine ​​is added to the obtained oxidized pullulan solution, the pH environment remains unchanged (pH=5.5), and the condensation reaction is carried out for 6 hours under room temperature (22°C) to form a thioketone bond; finally, 50 g of diaminopolyethylene glycol is added to the condensed pullulan solution, and a connection reaction is carried out for 4 hours to obtain a pullulan molecule with weak head-to-tail connection cyclization.

[0032] Finally, the cyclized pullulan solution was purified by dialysis ultrafiltration to remove unreacted reagents, and the purity of the cyclized product was evaluated by high performance liquid chromatography. The product with a purity of 99% or above was qualified and set aside.

[0033] Example 2 This embodiment is for preparing a kind of pullulan hollow capsule. As proposed in Example 1, although high molecular weight pullulan is used as raw material to ensure the impact resistance of the capsule shell, cross-linking and entanglement are easily present between high molecular weight pullulan molecules, strong friction and electrostatic effects exist inside the glue, the glue has high viscosity and poor dispersibility, which affects the surface microstructure of film formation. To solve this problem, the present invention uses small molecule pullulan as raw material to prepare pullulan hollow capsules. The pullulan used in this embodiment is the enzyme-treated small molecule pullulan described in Example 1 or the directly purchased small molecule pullulan with an average molecular weight of about 300,000 Daltons. The specific preparation process is as follows: 30g of gelling agent (gellan gum) was added to 134.6g of cold pure water and stirred until dissolved at a stirring speed of 100r / min; then the solution was heated to 95°C and incubated for 1h, 0.4g of moisturizer (glycerol) and 35g of lubricant (sucrose ester) were added and stirred until completely dissolved, and then 800g of pullulan (pullulan with a molecular weight range of 100,000 to 600,000 Daltons, of which pullulan below 100,000 Daltons and above 500,000 Daltons accounted for no more than 20%, and the average molecular weight was 250,000 to 350,000 Daltons) was added, stirred evenly (100r / min), and incubated for 4 hours, stirred once every hour, and after the pullulan was completely dissolved, it was kept stable at 55°C for 2h, and finally the glue liquid was dipped into a mold to form it, and dried at a temperature of 42°C for 30min to obtain a capsule cap body rubber blank, and demolded, cut, and fitted using a demolding device to obtain a pullulan hollow capsule 1 (referred to as hollow capsule 1).

[0034] Example 3 This embodiment is also for preparing a pullulan hollow capsule. It is found through experiments that the conductivity of pullulan affects the roughness of the capsule surface, and the conductivity of the 20% pullulan solution is set at 0.1 ms / cm to 0.8 ms / cm, which can further improve the surface smoothness of the capsule.

[0035] In this embodiment, except for controlling the conductivity of pullulan polysaccharide, the dosage of components and the preparation method are consistent with those in Example 2, and pullulan hollow capsules 2 (referred to as hollow capsules 2) are obtained.

[0036] In this embodiment, an ultrafiltration device is used to separate impurities from the pullulan solution. After testing, the conductivity of the obtained pullulan solution is 0.4ms / cm. In this embodiment, the surface microstructure of the hollow capsule 2 is also tested by electron microscopy. Figure 2 shown.

[0037] Example 4 This embodiment is also for preparing a pullulan hollow capsule.

[0038] In this embodiment, except that the pullulan used was the cyclized pullulan prepared in Example 1, the amount of components and the preparation method were the same as those in Example 2, and a pullulan hollow capsule 3 (referred to as hollow capsule 3) was obtained. The electron microscopy results are as follows: Figure 3 shown.

[0039] Example 5 This embodiment is also for preparing a pullulan hollow capsule.

[0040] In this embodiment, the pullulan polysaccharide used is the cyclized pullulan polysaccharide prepared in Example 1, and its conductivity is controlled. The dosage of the components and the preparation method are consistent with those in Example 2, and a pullulan hollow capsule 4 (referred to as hollow capsule 4) is obtained. The electron microscopy results are as follows: Figure 4 shown.

[0041] The conductivity of the pullulan used in this embodiment is also 0.4 ms / cm, and the control method of its conductivity is consistent with that of Example 3.

[0042] Example 6 This example investigates the surface smoothness of hollow capsules 1 to 4 prepared in Examples 2 to 5. In order to verify the influence of the molecular weight, conductivity, and molecular configuration of pullulan on the surface smoothness of the prepared capsule shell, the following comparative examples are also set in this example: Comparative Example 1: Except that the molecular weight of pullulan polysaccharide is 771200 Daltons, the dosage of components and the preparation method are the same as those in Example 2 to obtain comparative pullulan hollow capsule 1 (referred to as comparative capsule 1).

[0043] Comparative Example 2: Pullulan polysaccharide with a molecular weight of 7712 million Daltons was used as a raw material, and its conductivity was controlled to 0.4 ms / cm. The component dosage and preparation method were consistent with Example 2 to obtain pullulan hollow capsule 2 (referred to as comparative capsule 2).

[0044] Comparative Example 3: Pullulan polysaccharide with a molecular weight of 7712 million Daltons was used as a raw material, and was treated by the cyclization method in Example 1. The specific treatment methods were also consistent with those in Example 1. The amounts of the remaining components for preparing the capsule shell and the preparation methods were consistent with those in Example 2, and pullulan hollow capsules 3 (referred to as comparative capsules 3) were obtained.

[0045] Comparative Example 4: Pullulan polysaccharide with a molecular weight of 7712 million Daltons was used as a raw material, and the cyclization method in Example 1 was used for treatment. The specific treatment method was also consistent with that in Example 1, and the conductivity was controlled to be 0.4 ms / cm. The amounts of the remaining components and the preparation methods for preparing the capsule shell were consistent with those in Example 2, and pullulan hollow capsules 4 (referred to as comparative capsules 4) were obtained.

[0046] Comparative Example 5: Pullulan polysaccharide with a molecular weight of 100,000 Daltons was used as a raw material, and the dosage of the components and the preparation method were consistent with those in Example 2 to obtain comparative pullulan hollow capsules 5 (referred to as comparative capsules 5).

[0047] Comparative Example 6: Pullulan with a molecular weight of 100,000 Daltons was used as a raw material, and was treated by the cyclization method in Example 1. The specific treatment methods were also consistent with those in Example 1. The amounts of the remaining components for preparing the capsule shell and the preparation methods were consistent with those in Example 2, and pullulan hollow capsules 6 (referred to as comparative capsules 6) were obtained.

[0048] Comparative Example 7: The components and dosages are the same as those in Example 3, except that the conductivity of pullulan is controlled to be 0.05 ms / cm. The dosages and preparation methods of the remaining components for preparing the capsule shell are the same as those in Example 2, and pullulan hollow capsule 7 (referred to as comparative capsule 7) is obtained.

[0049] Comparative Example 8: The components and dosages are the same as those in Example 3, except that the conductivity of pullulan is controlled to be 1.2 ms / cm. The dosages and preparation methods of the remaining components for preparing the capsule shell are the same as those in Example 2, and pullulan hollow capsules 8 (referred to as comparative capsules 8) are obtained.

[0050] Comparative Example 9: The components and dosages are the same as those in Example 5, except that the conductivity of pullulan is controlled to be 0.05 ms / cm. The dosages and preparation methods of the remaining components for preparing the capsule shell are the same as those in Example 2, and pullulan hollow capsules 9 (referred to as comparative capsules 9) are obtained.

[0051] Comparative Example 10: The components and dosages are the same as those in Example 5, except that the conductivity of pullulan is controlled to be 1.2 ms / cm. The dosages of the other components and the preparation method for preparing the capsule shell are the same as those in Example 2, and a pullulan hollow capsule 10 (referred to as comparative capsule 10) is obtained. The electron microscopy test results are as follows: Figure 5 shown.

[0052] In this embodiment, the surface friction, surface smoothness and mechanical properties of the prepared capsule shell are used as evaluation indicators. Among them: The surface friction of the capsule shell is detected according to the method disclosed in the patent CN108548478B previously applied by our company. The slipperiness is expressed by the friction coefficient; the smaller the friction coefficient, the better the slipperiness.

[0053] The mechanical properties of the capsule shell are directly expressed by the friability. The testing method is based on the pharmacopoeia method. The friability standard is: <10%.

[0054] The test results of the performance of each capsule shell are shown in Table 1.

[0055] Table 1. Test results of capsule shell performance

[0056] The results in Table 1 show that the slipperiness is best when the molecular weight of pullulan is controlled between 100,000 and 600,000 Daltons, among which hollow capsule 4 (controlled molecular weight + controlled conductivity + cyclization) has the best slipperiness and no risk of capsule brittleness.

[0057] Example 7 This embodiment is to investigate the effect of the amount of the linker composition and the reaction conditions on the performance of the prepared cyclized pullulan. This embodiment uses the hollow capsule 4 prepared in Example 5 as the basis for investigation. In each investigated capsule shell, except for the different cyclized pullulan used, the remaining components and capsule preparation methods are consistent with Example 5. The cyclized pullulan of each hollow capsule is shown in Table 2.

[0058] Table 2. Cyclized pullulan used in various capsule shells

[0059] The above-mentioned cyclized pullulan 1-12 was used to prepare pullulan capsule samples 1-12 (product 1 is the hollow capsule 4 prepared in Example 5) according to the method of Example 2, and then the slip and mechanical properties of each sample were tested and evaluated according to the method of Example 6. This example also uses the surface friction, surface smoothness and brittleness of the capsule shell as the evaluation indicators. The test results are shown in Table 3.

[0060] Table 3. Performance test results of each hollow capsule sample

[0061] The results in Table 3 show that when the amount of sodium periodate is 0.05-0.1%, the smoothness and friability are both good; when the pH is controlled at 5.0-5.5, the reaction temperature is 0-8°C, and the reaction time is 16h, the smoothness and friability are both good.

[0062] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view. In addition, it should be understood that although this specification is described in accordance with the implementation mode, it does not include only one technical solution. This narrative mode of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-slippery pullulan hollow capsule, characterized in that: The conductivity of the pullulan polysaccharide used in the hollow capsule is controlled within the range of 0.1 ms / cm to 0.8 ms / cm.

2. The high-slippery pullulan hollow capsule according to claim 1, characterized in that: The hollow capsule is prepared from the following components by mass fraction: Pullulan 75~90wt%, Gel 0.5~5wt%, Moisturizer 0.01~0.15wt%, Lubricant 0.1~1wt%, The balance is pure water.

3. The high-slippery pullulan hollow capsule according to claim 2, characterized in that: The molecular weight of the pullulan is controlled at 100,000 to 600,000 Daltons, of which pullulan below 100,000 Daltons and above 500,000 Daltons accounts for no more than 20%, and the average molecular weight is 250,000 to 350,000 Daltons.

4. The high slipperiness pullulan empty capsule according to claim 3, characterized in that: The pullulan is a pullulan with a cyclized structure formed by treating a cyclization linker composition; The cyclization linker composition is composed of sodium periodate, cystine and diaminopolyethylene glycol, wherein: The dosage of sodium periodate is 0.01% to 0.1% of the weight of pullulan; The dosage of cystine is 1% to 5% of the weight of pullulan; The dosage of diamino polyethylene glycol is 5% to 10% of the weight of pullulan.

5. The high-slippery pullulan hollow capsule according to claim 4, characterized in that: In the cyclization linker composition, The amount of sodium periodate used is 0.01% to 0.05% of the weight of pullulan; The molecular weight of the diamino polyethylene glycol is 5k-10k Daltons.

6. The high-slippery pullulan hollow capsule according to claim 2, characterized in that: The gelling agent is one or a mixture of curdlan, gellan gum, carrageenan, locust bean gum, pectin, xanthan gum and konjac gum; The moisturizing agent is one or a mixture of glycerin, sorbitol, propylene glycol, fructose alcohol, triethyl citrate, and docusate sodium; The lubricant is one or a mixture of sodium stearyl fumarate, sucrose ester, corn starch, colloidal silicon dioxide, magnesium stearate, poloxamer, copovidone, and stearyl palmitate glyceryl.

7. A method for improving the slipperiness of pullulan hollow capsules, characterized in that: The process steps include: 1) Pullulan preparation: Prepare or directly weigh pullulan with a molecular weight range of 100,000 to 600,000 Daltons, wherein pullulan below 100,000 Daltons and above 500,000 Daltons accounts for no more than 20%, and the average molecular weight is 250,000 to 350,000 Daltons; use sodium periodate, cystine and diamino polyethylene glycol as a linker composition to treat the pullulan to form a cyclized structure; and detect its conductivity, which is controlled within the range of 0.1 ms / cm to 0.8 ms / cm; 2) Material ratio: Weigh 75-90wt% of pullulan with a cyclized structure, 0.5-5wt% of a gelling agent, 0.01-0.15wt% of a moisturizing agent, 0.1-1wt% of a lubricant, and the remainder of cold pure water, a total of 100 parts; 3) Preparation of glue: Add the gel to cold pure water and stir, raise the temperature to above 90°C and incubate for 30-90 minutes until it is completely dissolved, then add the moisturizer and lubricant and continue to stir until it is completely dissolved, finally add pullulan and incubate until it is completely dissolved to form a gel solution, keep it stable at 50-60°C and set aside; 4) Glue dipping molding: The stabilized glue liquid is dipped into a mold for molding, and quickly dried in an oven at 40-45°C for 20-60 minutes to obtain a capsule cap body rubber blank, which is demoulded, cut and fitted using a demoulder to obtain a high-slippery pullulan hollow capsule.

8. The method for improving the slipperiness of pullulan empty capsules according to claim 7, characterized in that: In step 1), the process of using sodium periodate, cystine and diamino polyethylene glycol as a linker composition to treat pullulan to form a cyclized structure is as follows: 1-1) dissolving pullulan in distilled water, adding 0.01% to 0.5% sodium periodate by weight of pullulan, controlling the reaction temperature to 0 to 8°C, the pH value to 5.0 to 5.5, and reacting for 6 to 20 hours under light-shielding conditions. After the reaction is completed, removing unreacted sodium periodate to obtain an oxidized pullulan solution; 1-2) adding cystine in an amount of 1% to 5% by weight of the pullulan to the oxidized pullulan solution, carrying out a condensation reaction for 4 to 8 hours at room temperature while keeping the pH constant, to form a condensed pullulan solution; 1-3) Adding 5% to 10% of the weight of pullulan diaminopolyethylene glycol to the condensed pullulan solution and reacting for 2 to 6 hours to obtain a pullulan molecule with weak head-to-tail cyclization; 1-4) Purify the cyclized pullulan and test the product to ensure that its purity is 99% or above for later use.

9. The method for improving the slipperiness of pullulan empty capsules according to claim 7, characterized in that: In step 3), the specific process of preparing the glue solution is as follows: 3-1) Add the gelling agent into cold pure water and stir until dissolved at a stirring speed of 60-120 r / min, then heat the solution to above 90°C and incubate for 1 hour; 3-2) Add moisturizer and lubricant, stir until completely dissolved, stirring speed is 60-120r / min; 3-3) Add the cyclized pullulan, stir evenly and incubate for 4 to 5 hours, stirring once every hour at a stirring speed of 60 to 120 r / min; 3-4) After the pullulan is completely dissolved, keep it at 50-60℃ for 2-3 hours to prepare for dipping and molding.

10. The method for improving the slipperiness of pullulan empty capsules according to claim 9, characterized in that: In step 3-1), the temperature for dissolving and incubating the gel is 90-98°C.

Citation Information

Patent Citations

  • A method for quantifying capsule surface smoothness

    CN108548478B

  • Pullulan polysaccharide hollow hard capasule and its preparing method

    CN101069677A

  • Empty capsule capable of controlling disintegration time limit, and preparation method thereof

    CN103877067A

  • Pullulan polysaccharide capsule and preparation process thereof

    CN104436204A

  • Redox-sensitive core-crosslinked Pulullan nano particle having dual-targeting property and preparation method thereof

    CN106727423A